2008
DOI: 10.1672/07-105.1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling soil moisture effects on net nitrogen mineralization in loamy wetland soils

Abstract: Nutrient dynamics in wetland ecosystems are largely controlled by soil moisture content. Therefore, the influence of soil moisture content on N mineralization should be explicitly taken into account in hydro-ecological models. The aim of this research was to establish relationships between N mineralization and soil moisture content in loamy to silty textured soils of floodplain wetlands in central Belgium. Large undisturbed soil cores were taken, incubated for 3 months under various moisture contents, and zero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 26 publications
2
26
1
Order By: Relevance
“…The results in the UPF corresponded to the general established patterns of N availability in forest soils [12][13][14][15][16]18]. For example, net N transformation rates increased with soil temperature and SWC (Table 2, Figure 2).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The results in the UPF corresponded to the general established patterns of N availability in forest soils [12][13][14][15][16]18]. For example, net N transformation rates increased with soil temperature and SWC (Table 2, Figure 2).…”
Section: Discussionsupporting
confidence: 69%
“…Environmental controls of N mineralization and availability, particularly temperature and soil moisture, have been investigated through a theoretical model [11], literature review [9,12], laboratory experiments [13][14][15], and field manipulations [16][17][18][19]. For example, soil moisture varies significantly in space and time, and affects various biogeochemical processes in different ways [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that water (Stanford et al, 1974;Myers et al, 1982;Franzluebbers, 1999;Sleutel et al, 2008) and that the optimum 9 for N mineralization is commonly near field capacity (Linn and Doran, 1984). Although the specific shape of the tesponse of N mineralization rate to 9 is still under debate, a new biophysical watet ftinction which takes into account surface reactions and pore volume filling was recently proposed 201 lb).…”
Section: Relative Importance Of Soil Temperature and Water Content Inmentioning
confidence: 99%
“…The effect of soil water content on respiration or net soil N mineralization has been described using water content expressed as matric potential (Orchard and Cook, 1983;Sierra, 1997), gravimetric or volumetric water content (Stanford and Epstein, 1974;Wildung et al, 1975), fractions of water holding capacity (Howard and Howard, 1993;Ishaque and Cornfield, 1972), water-filled pore space (Doran et al, 1991;Drury et al, 2003;Franzluebbers, 1999;Sleutel et al, 2008), precipitation indices (Raich and Potter, 1995), depth to water table (Oberbauer et al, 1992), and relative water content between a minimum and a maximum value (Myers et al, 1982;Paul et al, 2003). Several relationships have been proposed for relating N mineralization to soil water content.…”
Section: Introductionmentioning
confidence: 99%
“…De Neve and Hofman (2002) concluded that simple linear or quadratic functions cannot be used to describe the effect of soil water on net N mineralization over a wide range of water contents. Several researchers have concluded that a logistic or a Gaussian function seems more suitable for deriving a relationship between water content and net N mineralization, and both functions yield parameters that have biological significance (Cassman and Munns, 1980;Gonçalvez and Carlyle, 1994;Reichman et al, 1966;Sleutel et al, 2008). The logistic function parameters are the minimum and maximum net N mineralization rates and the Gaussian parameters are the mineralization rate at optimum soil water content, the optimum soil water content and a moisture-dependence parameter (De Neve and Hofman, 2002).…”
Section: Introductionmentioning
confidence: 99%